Minimal access surgery for multiorgan hydatid cysts - Parelkar Sandesh; Sanghvi Beejal; Gupta Rahul; Agrawal Amit; Joshi Milind; Mishra Pankaj (Wolters Kluwer Medknow Publications, 2010)
Multiorgan hydatid cysts caused by larval growth of Echinococcus granulosus, is a rare condition in paediatric age group. There are very few reports of management of multiorgan hydatid cysts, involving lung, liver, and spleen by minimally invasive approach in paediatric age group. Herewith, we are reporting a case of hydatid cysts involving lung, liver, and spleen in a six-year-old child managed by minimally invasive surgery along with the review of literature.